Evaluation of Efficacy of BovEasy Bovine Rapid Pregnancy Detection Kits in Crossbred Cattle - Parmar, Chirag P; Devmurari, Yash J; Lunagariya, Pravin M.; Pathan, Mohsinkhan M; Patel, Richa M; Sarvaiya, Nitesh P (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Bovine early pregnancy detection is a boon to optimize reproductive rhythm and economic dairy entrepreneur. This study evaluated the efficacy of different early pregnancy detection methods in crossbred cows on the University Farm. In all 80 freshly inseminated crossbred cattle, which did not return to estrus within 22 days post-mid-estrus AI were included in the study. Blood samples were collected in EDTA/ clot activator vaccutainers on days 21, 28, 32, 36, and 45 post-AI for various tests. Transrectal ultrasonography was performed on day 28 post-AI at random on 45 animals. BovEasy bovine rapid PD kits were used on fresh whole blood on days 28, 32 and 36. Blood plasma samples were analyzed for progesterone by RIA technique on all days, and for pregnancy associated glycoproteins (PAGs) on day 28 and 36 post-AI by using ELISA kits. Final pregnancy was confirmed by actual per rectal palpation on day 45 post-AI. Out of 80 cows, 38 (57.50 %) were confirmed to be pregnant by day 45 post-AI. However, by early PD kits, the animals declared pregnant on days 28, 32 and 36 were 41, 40 and 40, respectively, with suspicious results in 5, 2 and 2 animals. The accuracy, specificity and sensitivity of rapid test kits recorded were 93.75, 95.24 and 92.00% on day 28 post-AI, and 97.50, 97.62 and 97.00% on day 32 as well as 36 post-AI, respectively. The plasma progesterone concentrations showed a significant (p<0.05) increase in the levels from day 21 to day 45 in conceived subgroup with significantly higher values than in non-conceived subgroup. The plasma PAG in conceived subgroup was significantly (p<0.001) higher than in non-conceived subgroup on both the days of testing, with around 1.5 to 1.7-fold increase on day 36 compared to day 28 in conceived subgroup. The accuracy of positive pregnancy on day 28 post-breeding was 100% by both plasma progesterone and USG, and 97% by plasma PAGs. The study also recorded 10.00% early embryonic mortality in crossbred cattle.